3D semantic models for dental education - Dias, Diego Roberto Colombo [UNESP]; Brega, José Remo Ferreira [UNESP]; De Paiva Guimarães, Marcelo; Modesto, Fábio; Gnecco, Bruno Barberi; Lauris, José Roberto Pereira (Springer Nature, 2011)
This paper explores the benefits of using immersive and interactive virtual reality environments to teach Dentistry. We present a tool for educators to manipulate and edit virtual models. One of the main contributions is that multimedia information can be semantically associated with parts of the model, through an ontology, enriching the experience; for example, videos can be linked to each tooth demonstrating how to extract them. The use of semantic information gives a greater flexibility to the models, since filters can be applied to create temporary models that show subsets of the original data in a human friendly way. We also explain how the software was written to run in arbitrary multi-projection environments. © 2011 Springer-Verlag.
Keywords: Dentistry; Semantic Model; Virtual Reality; Human-friendly; Immersive; Interactive virtual reality; Multimedia information; Semantic information; Virtual models; Information systems; Ontology; Semantics; User interfaces; Virtual reality; Three dimensional